Pengaruh Pemberian Edukasi Kesiapsiagaan Bencana Gempa Bumi Pada Lansia Di Kelurahan Parupuak Tabing Kota Padang - Fitri Mailani; Fadilah Lukvianti; Yuanita Ananda (JINTAN: Jurnal Ilmu Keperawatan, 2023)
The elderly are one of the most vulnerable groups during a disaster. The vulnerability of this group is caused by physical and mental changes in the elderly. These changes can cause the elderly to become victims of a disaster. To reduce the impact for disaster of elderly fatalities, it is necessary to educate them on how to save themselves when a disaster occurs. The purpose of this nursing care is to increase the knowledge of the elderly in self-rescue during an earthquake. Nursing care was carried out with a quasi-experimental pretest-posttest on 15 elderly people in RW 17 Parupuak Tabing Village. Nursing care will be carried out from November to December 2022 by providing earthquake preparedness education using pamphlets. The result of providing nursing care was an increase in the knowledge of the elderly after being given education about disaster preparedness, with an average pre-test score of 2.27 and a post-test average score of 7.13. The increase in the average pre-test and post-test was 4.86 with a value (p value = 0,000). This means that there is an educational influence on the knowledge of the elderly about how to save themselves when an earthquake occurs. It is hoped that the BPBD will develop plans and activities focused on increasing knowledge to respond to disaster risks by providing education and training for the elderly.